Respiratory Sinus Arrhythmia in Children—Predictable or Random? - Lubocka, Paulina; Sabiniewicz, Robert (Frontiers in Cardiovascular Medicine, 2021)
Background: Respiratory sinus arrhythmia (RSA) is associated with better health in children. Aim: The study was conducted to analyze the trajectory of RSA in 10-year-olds. Methods: A follow-up study on 120 healthy children (62 boys) aged 10,7 +/- 0,5 years consisted of a standard 12-lead electrocardiogram, measurements of height, weight and blood pressure. The protocol was repeated after three years. Assessment of RSA based on semi-automatic measurements of RR intervals included pvRSA, RMSSD, SDNN and their equivalents corrected for heart rate. Results: A the first visit 61.7% of children presented with RSA; 51.7% 3 years later. 23.3% of them had RSA only on the first examination; 13.3% only on the second one. The pvRSA, RMSSD and SDNN measured in 2019 did not differ significantly from their 2016 equivalents (p>0.05). The decline in RSA defined by RMSSD was noted in 52.5% of children and in 54.2% when defined by SDNN. The corrected values decreased in 68.3% and 64.2% of the participants for RMSSDc and SDNNc respectively. The students with RSA at both visits had lower heart rate (p<0.001) and systolic blood pressure (p=0.010) compared to those with rhythmic electrocardiograms. Conclusions: RSA in children is changeable, though its measurable indices should be adjusted to heart rate.